VIEWING ENGLISH LEARNING THROUGH THE EYES OF SPECIAL NEEDS STUDENTS: A NARRATIVE INQUIRY ON VR IMPLEMENTATION WITH MILLEALAB [MELIHAT PEMBELAJARAN BAHASA INGGRIS MELALUI PERSPEKTIF SISWA BERKEBUTUHAN KHUSUS: SEBUAH PENELITIAN NARATIF TENTANG IMPLEMENTASI VR DENGAN MILLEALAB] - Ananda, Dheta; Wulandari, Sri; Kurniawan, Erwin Hari (Polyglot, 2025)
This research is focused on the implementation of the MilleaLab VR platform for teaching English to a student with ADHD at SMP Plus Rahmat, Kediri, Indonesia. Traditional methodologies in teaching are often less engaging for students with ADHD, and alternative methods are increasingly needed. That is where Virtual Reality comes in. MilleaLab can offer an interactive learning environment that takes away stress, maintains focus, and increases interest in learning. After going through Narrative Inquiry, one could deduce that the participant was interested in learning because of the enrichment through Virtual Reality learning. The student was very keen to learn and was more relaxed when it came to learning English; this meant that Virtual Reality did have some advantage over its rivals. The student showed a more profound understanding of the stories told during the classes and seemed to remember them more; this would mean that VR can significantly improve memory and understanding. This points to the need to offer teaching techniques relevant to each individual for the students to continue their studies with success. These findings point out Virtual Reality as the preferred method of teaching, where the student mentioned the desire to continue working on MilleaLab. The results form an emerging understanding of the place of VR within inclusive education and point to some potentially productive directions for further research into the use of technology within diverse learning environments. Abstrak bahasa Indonesia Penelitian ini berfokus pada penerapan platform VR MilleaLab dalam pengajaran bahasa Inggris kepada seorang siswa dengan ADHD di SMP Plus Rahmat, Kediri, Indonesia. Metode pengajaran tradisional yang sering kurang menarik bagi siswa dengan ADHD membutuhkan alternatif yang lebih inovatif, dan di sinilah Virtual Reality (VR) berperan. MilleaLab menyediakan lingkungan pembelajaran interaktif yang dapat mengurangi stres, menjaga fokus, dan meningkatkan minat belajar. Melalui pendekatan *Narrative Inquiry*, ditemukan bahwa siswa menunjukkan antusiasme lebih tinggi, merasa lebih rileks, dan memiliki pemahaman yang lebih mendalam terhadap materi pelajaran, terutama dalam mengingat cerita yang disampaikan selama pembelajaran. Hal ini mengindikasikan bahwa VR dapat secara signifikan meningkatkan daya ingat dan pemahaman, sekaligus menunjukkan keunggulan dibandingkan metode pembelajaran lainnya. Siswa juga menyatakan keinginan untuk terus belajar menggunakan MilleaLab, yang menguatkan potensi VR sebagai metode pengajaran yang relevan untuk kebutuhan individu, khususnya dalam pendidikan inklusif. Hasil penelitian ini memberikan pemahaman yang lebih luas tentang peran VR dalam mendukung keberhasilan belajar siswa dengan kebutuhan khusus dan membuka peluang untuk penelitian lebih lanjut mengenai teknologi dalam lingkungan pembelajaran yang beragam.